HUBUNGAN KONDISI SOSIAL EKONOMI MASYARAKAT PERAMBAH HUTAN DENGAN POLA PENGGUNAAN LAHAN DI TAMAN NASIONAL BUKIT BARISAN SELATAN - Pasha, Rachman; Susanto, Agus (Jurnal Organisasi Dan Manajemen, 2009)
One of the problems that faced by national parks in Indonesia is encroachment. In many cases, most of the problems were caused by the high level of community dependency on the natural resources around the area. The Bukit Barisan National Park (TNBBS) with a total area of 365,000 ha was also has similar problems. Considering this problems, we need an effort to solve the problems by addressing these issues by reviewing socio-economic characteristics of encroacher who live at TNBBS first. This study is expected could provide the alternative strategies in order to overcome the encroachment problems in TNBBS in the future.This study will closely look at the relationship between socio economic conditions of encroacher with they land use pattern in TNBBS by taking some of the socio-economic parameters, such as family size, age, education level, income level, periods of living and number of plots occupied land. The data will be analyzed by using Multiple Regression Analysis method, Biplot Method and descriptive tabulation method.